Improving permanent pasture's growth: An organic approach - Colmenares R.; Miguel J.-M. de (Dynamics and sustainability of Mediterranean pastoral systems, 1999)
Within the framework of organic agriculture there exists the biodynamic school of agriculture. The effect of the application of biodynamic preparations on permanent pastures along the altitudinal gradient in the NW of Madrid is presented here. During a period of three and a half years on experimental plots established on three different commercial farms two parameters on pasture growth were monitored: pasture yield and pasture dry matter content. The results obtained suggest that biodynamic preparations enhance an optimal development rather than just growth, i.e. focusing on improving pasture quality rather than just its quantity.
9. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Pastures and Fodder Crops, 1997/11/26-29, Badajoz (Spain)